First Experiences of Patients and Healthcare Professionals with Routine Use of Patient-Reported Outcome Measures for Venous Thromboembolism - de Jong, Cindy M.M.; ter Haar, Sophie N.M.; Bos, Willem Jan W.; den Exter, Paul L.; Huisman, Menno V.; Kosterink, Marlon H.C.; van Mens, Thijs E.; Klok, Frederikus A. (TH Open, 2025)
Venous thromboembolism (VTE) can considerably limit patients' functioning and quality of life. Using patient-reported outcome measures (PROMs), the full impact of VTE on individual patients can be captured.To evaluate the experiences of patients and healthcare professionals with the routine use of PROMs for VTE patients visiting the outpatient clinic, a mixed-methods study was performed at Leiden University Medical Center, the Netherlands. VTE PROMs were incorporated into routine care since March 2023, through a digital application sending patients invitations to complete PROMs. Quantitative and qualitative data were obtained from semi-structured interviews with patients and involved healthcare professionals. The NoMAD (normalization measure development) questionnaire was used to assess the implementation process from the professionals' perspective. Patients aged ≥18 years who experienced VTE and completed PROMs at two follow-up time points during ≥3 months follow-up and VTE patients who did not complete PROMs at both time points were asked to participate.Eight patients (five completed PROMs; three did not) and four professionals were interviewed. Both patients and professionals experienced the use of PROMs as neutral to predominantly positive (lower limit 3 on a scale of 1–5). All professionals valued the effects of PROMs on their work. Most patients felt the questionnaires contained too many questions. Suggestions to improve the completion rate, accessibility, PROMs content, and the digital tool were shared.PROMs were believed to provide additional value during preparation for the appointment and during the consultation. The first experiences of patients and professionals, tending toward positive, can be used to improve PROMs application and support implementation in routine thrombosis care.
Keywords: venous thromboembolism; patient-reported outcome measures; patient-centered care; patient outcome assessment; implementation science